ENTREPRENEURIAL EDUCATION AND ATTITUDES OF UNIVERSITY GRADUATES AS A TOOL FOR SELF-RELIANCE IN NIGERIA - Mohammed, Idris Abdullahi (Institute of Advanced Engineering and Science, 2020)
Entrepreneurial Education has been globally apprehended as a weapon empowering graduates for sustainable livelihood and socio-economic independence, which measures greatly in accordance with the behavioral characteristics of the graduates towards comprehending and applying the entrepreneurial knowledge and skills acquired through the university training programs. This study aimed at investigating the relevance of entrepreneurial education and attitudes as a means for sustainable socio-economic self-independence of university graduates in Nigeria. The perception is that, through entrepreneurial education and positive attitudes, the graduates will pass-out and pursue different careers as independent entrepreneurs within the socio-economic society. Entrepreneurship education has the potential to enable graduates to gain the necessary knowledge and skills to independently create their own jobs. Existing empirical and conceptual and theoretical literature was surveyed and analyzed to gather relevant and satisfactory information about entrepreneurial education?s influence on the attitudes of the graduates towards determination for occupational self-reliance, thereby consequently gaining economic self-independence in achieving the progress of the individual graduate in particular and that of the society in general